2010
DOI: 10.1111/j.1095-8649.2009.02502.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated water temperature impairs fertilization and embryonic development of whitefish Coregonus lavaretus

Abstract: The adverse effects of high temperatures on the early life stages of anadromous whitefish Coregonus lavaretus were experimentally examined by assessing fertilization success, the percentage of developmental abnormalities, cumulative mortality and the rate of embryogenesis across a range of temperatures. Temperatures >or= 7 degrees C increased the proportion of unfertilized and abnormally dividing eggs, deformed embryos and consequent mortality. The higher the temperature, the more severe were the effects. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 42 publications
4
35
0
1
Order By: Relevance
“…Spawning activity and the mRNA expression levels of gonadotropins were impaired by elevated water temperatures in both sexes of the pejerrey (Elisio et al 2012, Soria et al 2008. Water temperature elevation during the spawning season increased the proportion of unfertilized and abnormally dividing eggs in the whitefish, Coregonus lavaretus, leading to increased mortality of early-stage fish (Cingi et al 2010). Early in their life cycles, fish are highly sensitive to various environmental factors, including mineral balances, pH, heavy metals, and oxygen (Finn 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Spawning activity and the mRNA expression levels of gonadotropins were impaired by elevated water temperatures in both sexes of the pejerrey (Elisio et al 2012, Soria et al 2008. Water temperature elevation during the spawning season increased the proportion of unfertilized and abnormally dividing eggs in the whitefish, Coregonus lavaretus, leading to increased mortality of early-stage fish (Cingi et al 2010). Early in their life cycles, fish are highly sensitive to various environmental factors, including mineral balances, pH, heavy metals, and oxygen (Finn 2007).…”
Section: Discussionmentioning
confidence: 99%
“…1), as demonstrated for a few specimens tagged with transponders that last for periods up to 4 years. Development of eggs from spawning until hatching was estimated in terms of day degrees (i.e., the sum of daily mean temperatures) for anadromous C. lavaretus with a mean (50% hatching) at 455 AE 20°C and a start (i.e., 10% hatching) at 413 AE 27°C (Cingi et al 2010). In this fourth season, abundance of NSH larvae peaked around the 17th of March 2010.…”
Section: Discussionmentioning
confidence: 99%
“…comm.). Furthermore, experimental studies have demonstrated the negative effects of temperatures >7 °C on the success of fertilization, viability of eggs, and survival of embryos (Cingi et al 2010). During the spawning season, water temperatures exceeding 8 °C, as are expected due to climate change, will likely cause a decline in whitefish reproductive success (Gillet 1991, Anneville et al 2013.…”
Section: Implication Of Climate Variability and Fisheries Management mentioning
confidence: 99%